2013
DOI: 10.1071/mf12106
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ways to combat eutrophication in a Chinese drinking water reservoir using SWAT

Abstract: Abstract. Across China, nutrient losses associated with agricultural production and domestic sewage have triggered eutrophication, and local managers are challenged to comply with drinking water quality requirements. Evidently, the improvement of water quality should be targeted holistically and encompass both point sources and surface activities within the watershed of a reservoir. We expanded the ordinary Soil Water Assessment Tool -(SWAT) with a widely used empirical equation to estimate total phosphorus (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…OP loading was a significant (p < 0.05) predictor of OP concentrations in all four reservoirs. Nielsen et al (2013) observed a similar linear relationship between SWAT-generated phosphate loading and total phosphate concentrations in a reservoir in China. The regression and 95 % prediction limits allow for the estimation of annual loading limits that ensure mean annual OP concentrations fall below certain trophic status indicators.…”
Section: Impact Of Op Effluent Standard Scenarios On Trophic Statussupporting
confidence: 57%
“…OP loading was a significant (p < 0.05) predictor of OP concentrations in all four reservoirs. Nielsen et al (2013) observed a similar linear relationship between SWAT-generated phosphate loading and total phosphate concentrations in a reservoir in China. The regression and 95 % prediction limits allow for the estimation of annual loading limits that ensure mean annual OP concentrations fall below certain trophic status indicators.…”
Section: Impact Of Op Effluent Standard Scenarios On Trophic Statussupporting
confidence: 57%
“…Nielsen et al, 2013). The SWAT model is physically based and provides distributed descriptions of hydrologic processes at sub-basin scale (Arnold et al, 1998;Neitsch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lake management was also the subject of modelling work done to mitigate P loads and maintain drinking water quality in the subtropical Kaiping (Dashahe) reservoir in China (Nielsen et al 2013). By adapting a surface water catchment model, a powerful scenario analysis was conducted of different mitigation technologies and practices.…”
Section: Linking Nutrient Losses To Effects and Management Across Scalesmentioning
confidence: 99%